Cognitive Interventions Based on Technology: A Systematic Literature Review - Ramos-Galarza, Carlos (2021)
This article reports a systematic review of research done about the positive impact of cognitive treatment for people with some type of brain disorder through the use of inclusive technologies. The article collected 21 publications of high impact magazines uncovering that countries such as Spain, France, and Russia have a significant number of contributions on this topic. Inclusive technological innovations which are intended for work on brain functions such as attention, memory, verbal fluency, problem-solving and behavior regulation have been mainly developed in devices such as Tablets and Robots. The data discussed highlights the need to continue in this line of research to determine the effect of this type of intervention, as well as the future projection of developing new technological devices facilitating human brain functions